Identification of watermelon heat shock protein members and tissue-specific gene expression analysis under combined drought and heat stresses - ALTUNOĞLU, Yasemin Çelik; KELEŞ, Merve; CAN, Tevfik Hasan; BALOĞLU, Mehmet Cengiz (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2019)
Heat shock protein (Hsp) gene family members in the watermelon genome were identified and characterized by bioinformatics analysis. In addition, expression profiles of genes under combined drought and heat stress conditions were experimentally analyzed. In the watermelon genome, 39 genes belonging to the sHsp family, 101 genes belonging to the Hsp40 family, 23 genes belonging to the Hsp60 family, 12 genes belonging to the Hsp70 family, 6 genes belonging to the Hsp90 family, and 102 genes belonging to the Hsp100 family were found. It was also observed that the proteins in the same cluster in the phylogenetic trees had similar motif patterns. When the estimated 3-dimensional structures of the Hsp proteins were examined, it was determined that the α-helical structure was dominant in almost all families. The most orthologous relationship appeared to be between watermelon, soybean, and poplar in the ClaHsp gene families. For tissue-specific gene expression analysis under combined stress conditions, expression analysis of one representative Hsp gene each from root, stem, leaf, and shoot tissues was performed by real-time PCR. A significant increase was detected usually at 30 min in almost all tissues. This study provides extensive information for watermelon Hsps, and can enhance our knowledge about the relationships between Hsp genes and combined stresses.
Keywords: Article; 15. Life on land; 6. Clean water